2006
DOI: 10.1111/j.1469-0691.2006.01437.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Chlamydia trachomatis DNA using MagNA Pure DNA extraction and Cobas Amplicor CT/NG amplification

Abstract: The automated MagNA Pure DNA extraction method for Chlamydia trachomatis was compared with the manual Cobas Amplicor protocol using 100 microL of input sample volume from 964 specimens. Agreement between protocols was 96.1%. The automated extraction method had a sensitivity of 99% and a specificity of 100%. Amplification inhibition observed after manual preparation of samples (3.8%) was not apparent following automated extraction. Using 200 microL of sample in the automated extraction process lowered the detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 10 publications
0
9
2
Order By: Relevance
“…There are very few reports of ESBL production by DEC [31-33]. DEC isolates in these studies were found to harbor bla CTX-M [31-33], bla TEM [32,33] or bla PER genes [33]. In Kuwait, children with invasive diarrhea are normally treated with third generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…There are very few reports of ESBL production by DEC [31-33]. DEC isolates in these studies were found to harbor bla CTX-M [31-33], bla TEM [32,33] or bla PER genes [33]. In Kuwait, children with invasive diarrhea are normally treated with third generation cephalosporins.…”
Section: Discussionmentioning
confidence: 99%
“…However, these calculations are not ideal because the method used for comparison (LightMix) only detects the omp1 gene. Furthermore, the CE Mark-certified protocol was slightly modified; however, these modifications were previously evaluated and may even represent optimisations 712. Three CTM CT v2.0 low positive samples were not confirmed using BD ProbeTec ET or the new Abbott m 2000rt CT II assay.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical samples were extracted by using the automated MagNA Pure DNA extraction (Roche Diagnostics, Meylan, France) [14] then analysed using a Chlamydiaceae-specific real-time PCR targeting the 23S rRNA gene [15] and a specific incA real-time PCR protocol [16].…”
Section: Direct Detection Of Chlamydia Psittaci From Human Samplesmentioning
confidence: 99%